Immune Predictors of Mortality After Ribonucleic Acid Virus Infection. (17th October 2019) - Graham, Jessica B; Swarts, Jessica L; Menachery, Vineet D; Gralinski, Lisa E; Schäfer, Alexandra; Plante, Kenneth S; Morrison, Clayton R; Voss, Kathleen M; Green, Richard; Choonoo, Gabrielle; Jeng, Sophia; Miller, Darla R; et al.
Abstract: Background: Virus infections result in a range of clinical outcomes for the host, from asymptomatic to severe or even lethal disease. Despite global efforts to prevent and treat virus infections to limit morbidity and mortality, the continued emergence and re-emergence of new outbreaks as well as common infections such as influenza persist as a health threat. Challenges to the prevention of severe disease after virus infection include both a paucity of protective vaccines as well as the early identification of individuals with the highest risk that may require supportive treatment. Methods: We completed a screen of mice from the Collaborative Cross (CC) that we infected with influenza, severe acute respiratory syndrome-coronavirus, and West Nile virus. Results: The CC mice exhibited a range of disease manifestations upon infections, and we used this natural variation to identify strains with mortality after infection and strains exhibiting no mortality. We then used comprehensive preinfection immunophenotyping to identify global baseline immune correlates of protection from mortality to virus infection. Conclusions: These data suggest that immune phenotypes might be leveraged to identify humans at highest risk of adverse clinical outcomes upon infection, who may most benefit from intensive clinical interventions, in addition to providing insight for rational vaccine design. Abstract : We used a screen of genetically diverse mice from the Collaborative Cross infected with RNA viruses in combination with comprehensive preinfection immunophenotyping to identify baseline immune correlates of protection from mortality to virus infection.